Antimicrobial properties of hindered amine light stabilizers in polymer coating materials and their mechanism of action - Costa, Tiago; Sampaio-Marques, Belém; Neves, Nuno M.; Aguilar, Helena; Fraga, Alexandra G. (Frontiers in Bioengineering and Biotechnology, 2024)
UV-stabilizers are a class of additives that provide extended polymer resistance to UV-degradation, but have also been suggested to have antimicrobial activity, potentially preventing the spread of pathogens, and inhibiting microbial-induced biodegradation. In this work, we incorporated different UV-stabilizers, a hindered amine light stabilizer (HALS), Tinuvin 770 DF and Tinuvin PA 123, or a hybrid HALS/UV-absorber, Tinuvin 5151, in polyurethane formulations to produce lacquer-films, and tested their antimicrobial activity against Staphylococcus aureus (methicillin-resistant and -sensitive strains), Escherichia coli and Candida albicans. Lacquer-films incorporated with Tinuvin 770 DF showed strong antimicrobial performance against bacteria and fungi, while maintaining cytocompatibility. The mechanism of action revealed a positive relationship between Tinuvin 770 DF concentration, microbial death, and reactive nitrogen species (RNS), suggesting that RNS produced during autoxidation of Tinuvin 770 DF is responsible for the antimicrobial properties of this UV-stabilizer. Conversely, lacquer-films incorporated with Tinuvin 5151 or Tinuvin PA 123 exhibited no antimicrobial properties. Collectively, these results highlight the commercial potential of Tinuvin 770 DF to prevent photo- and biodegradation of polymers, while also inhibiting the spread of potentially harmful pathogens. Furthermore, we provide a better understanding of the mechanism underlying the biocidal activity of HALS associated to autooxidation of the amine group.